Accuracy and Reliability of Combining a Smartphone and a Digital Angle Ruler Technique to Assist Acetabular Cup Placement: A Pelvic Model Study - Uthaicharatratsame, MD, Charoenwat; Sahajarupat, MD, Somboon; Adullayathum, MD , Teerapat (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To examine the accuracy and reliability of a method that used a smartphone and a digital angle ruler for improving the acetabular cup placement in a pelvic model. Materials and Methods: An experimental study was conducted in a plastic pelvic model. During the cup placement at the target of radiographic inclination (RI) 40º and anteversion (RA) 15º verified by the Orthopilot navigation system, 3 orthopedic surgeons simultaneously assessed the cup orientation by a smartphone application for the anteversion and a digital angle ruler for the inclination. The surgeon-measured angles were calculated into the RI and RA values by Murray’s equation; and then used to compare with the target angle by the navigation system. Results: The mean RI and RA angles from the 3 surgeons were 40.08º ± 2.15º and 11.01º ± 0.35º, respectively. The mean differences between the RI and RA angles from the navigation system and those calculated from the combined devices were 0.80º ± 2.15º (-3.10º to 5.3º) and -3.98º ± 0.35º (-4.60º to -3.30º), respectively. Both intra-tester and inter-tester reliabilities were good to excellent in the assessment of the cup RI and RA. Conclusion: Use of smartphone application combined with a digital angle ruler could provide a high accuracy of acetabular cup positioning, especially for the inclination angle.